THE INFLUENCE OF TAX PLANNING AND PROFITABILITY ON PROFIT MANAGEMENT WITH INSTITUTIONAL OWNERSHIP AS A MODERATION VARIABLE (Empirical Study on Listed Energy Sector Companies on the Indonesian Stock Exchange 2020-2022) - Ni Kadek Jesika Diva Yanthi; Ni Luh Supadmi (Adisam Publisher, 2025)
Earnings management is an effort made by management to intervene in the preparation of financial reports with the aim of benefiting itself, namely the company concerned. This research aims to obtain empirical evidence regarding the influence of tax planning and profitability on earnings management with institutional ownership as a moderating variable. This research is based on agency theory. This research was conducted on energy sector companies listed on the Indonesia Stock Exchange in 2020-2022. The number of samples in this research was 24 companies with the sample collection method using a purposive sampling technique. The data analysis technique used in this research is Moderated Regression Analysis (MRA). The results of data analysis show that tax planning has an effect on earnings management and institutional ownership weakens the relationship between tax planning and earnings management. The theoretical implications of this research are able to support and increase knowledge related to the application of agency theory and positive accounting theory. The practical implication is that companies are expected to be able to carry out good tax planning and manage profits effectively and efficiently, while investors need to consider these factors in investment decisions.